2022
DOI: 10.3847/1538-4357/ac63c7
|View full text |Cite
|
Sign up to set email alerts
|

COMAP Early Science. V. Constraints and Forecasts at z ∼ 3

Abstract: We present the current state of models for the z ∼ 3 carbon monoxide (CO) line intensity signal targeted by the CO Mapping Array Project (COMAP) Pathfinder in the context of its early science results. Our fiducial model, relating dark matter halo properties to CO luminosities, informs parameter priors with empirical models of the galaxy–halo connection and previous CO (1–0) observations. The Pathfinder early science data spanning wavenumbers k = 0.051–0.62 Mpc−1 represent the first direct 3D constraint on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 83 publications
0
36
0
Order By: Relevance
“…This demonstrates that we are in fact averaging down the noise, as expected for uncorrelated noise, and that the various potential systematic errors are suppressed to a level below the noise. At this point in the COMAP survey, this is a key outcome, given that our fiducial theoretical model predicts a signal on the order of kP CO ∼ 10 3 μK 2 Mpc 2 at our target redshift (Chung et al 2022), well below the noise level shown here. This signal estimate is highly uncertain, however, and as discussed in Chung et al (2022) these data already rule out some of the most optimistic models.…”
mentioning
confidence: 50%
See 4 more Smart Citations
“…This demonstrates that we are in fact averaging down the noise, as expected for uncorrelated noise, and that the various potential systematic errors are suppressed to a level below the noise. At this point in the COMAP survey, this is a key outcome, given that our fiducial theoretical model predicts a signal on the order of kP CO ∼ 10 3 μK 2 Mpc 2 at our target redshift (Chung et al 2022), well below the noise level shown here. This signal estimate is highly uncertain, however, and as discussed in Chung et al (2022) these data already rule out some of the most optimistic models.…”
mentioning
confidence: 50%
“…At this point in the COMAP survey, this is a key outcome, given that our fiducial theoretical model predicts a signal on the order of kP CO ∼ 10 3 μK 2 Mpc 2 at our target redshift (Chung et al 2022), well below the noise level shown here. This signal estimate is highly uncertain, however, and as discussed in Chung et al (2022) these data already rule out some of the most optimistic models.…”
mentioning
confidence: 50%
See 3 more Smart Citations